State of the art: Evaluation and prognostication of myocarditis using cardiac MRI - Gannon, Michael P.; Schaub, Ebe; Grines, Cindy L.; Saba, Shahryar G. (Journal of magnetic resonance imaging, 2019)
Myocarditis encompasses both primary and secondary processes causing inflammation of the myocardium. Viral infections are a common secondary cause of myocarditis with important clinical relevance. Viral myocarditis has a varied clinical presentation, potentially resulting in significant morbidity and mortality. Acutely, systolic dysfunction and sudden cardiac death may ensue; chronically, myocarditis may result in a dilated cardiomyopathy requiring heart transplantation. Myocarditis is thought to be one of the most common causes of myocardial infarction with nonobstructive coronary arteries (MINOCA), with important consequences for cardiovascular outcomes. Patients with myocarditis are currently underdiagnosed. Cardiac MRI has evolved as the noninvasive test of choice, with cardiac MRI-specific diagnostic requirements defined in the Lake Louise Criteria (LLC). Detecting the presence of tissue edema, hyperemia, and necrosis in both acute and chronic stages form the foundation of the LLC. Cardiac MR for chronic myocarditis (greater than 8 weeks from symptom onset) has decreased sensitivity for diagnosis. Emerging sequences such as T1 and T2 parametric maps provide tissue characterization regarding inflammation without reliance on reference tissue, overcoming limitations of the LLC. Beyond diagnostic criteria, these imaging techniques have proven useful in further characterizing the diseased tissue, prognostication, and clinical decision-making. This review describes the utility and evolving use of cardiac MRI in clinical practice. Level of Evidence: 1 Technical Efficacy Stage: 5 J. Magn. Reson. Imaging 2018;47:1061-1071.